Periodic Perturbation Method for Controlling Chaos for a Positive Output DC-DC Luo Converter - P. Balamurugan; A. Kavitha; P. Sanjeevikumar; J.L. Febin Daya; Tole Sutikno (Institute of Advanced Engineering and Science, 2017)
A simple, non-feedback method of controlling chaos is implemented for a DC-DC converter. The weak periodic perturbation (WPP) is the control technique applied to stabilize an unstable orbit in a current-mode controlled Positive Output Luo (POL) DC-DC converter operating in a chaotic regime. With WPP, the operation of the converter is limited to stable period-1 orbit that exists in the original chaotic attractor. The proposed control strategy is implemented using simulations and the results are verified with hardware setup. The experimental results of the converter with WPP control are presented which shows the effectiveness of the control strategy.